Formulasi dan Uji Sifat Fisik Sediaan Krim dari Ekstrak Watermelon Rind ((Citrullus lanatus).(Thunb)). - Anisabeth Yan; Irma Novrianti; Faizal Mustamin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Indonesia has a tropical climate which makes the body produce excess oil. This triggers the occurrence of acne, because it can clog skin pores and cause the formation of bacterial colonies. Watermelon is a fruit that has many health benefits. Generally, people consume the contents and throw away the white flesh and skin (watermelon rind), even though this part has good benefits for the skin because it contains several biochemical compounds that act as antibacterial. One of the preparations used for skin problems is cream. This study aims to produce a formula for the preparation of watermelon rind extract cream that complies with pharmaceutical requirements and is stable in storage. Watermelon rind cream preparation is made with a concentration of watermelon rind extract, namely FI 7.5%; FII 12.5%, and FIII 20%. Finished preparations were tested for physical stability which included organoleptic tests, homogeneity, pH, irritation tests, cream type tests, spreadability and stability tests. The watermelon rind extract cream obtained is green in color, has a distinctive smell of extract and rose oil, is homogeneous, and is of the M/A type. The pH of the watermelon rind extract cream is in a range that is still acceptable to the skin and has good spreadability and does not cause irritation to the skin. During the storage period, the watermelon rind extract cream did not experience physical changes and homogeneity, and did not experience a significant decrease in pH and spreadability with a p-value > 0.05. This shows that the preparation of watermelon rind extract cream meets pharmaceutical requirements and is stable during storage.